Ruptured cornual ectopic pregnancy at 8 weeks gestation- successful conservative approach: a case report - Shiragur, Shobha S.; Gobbur R, Vijayalaxmi; Tehalia J, Manpreetkaur; Doshi, Rathi; Kori, Sreedevi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Cornual pregnancy is a rare form of ectopic pregnancy that usually leads to uterine rupture with resultant life threatening hemorrhage. The mortality of interstitial pregnancies is more than twice that of other tubal pregnancies. Cornual pregnancies often rupture later than other tubal pregnancies because the myometrium is more distensible than the fallopian tube. We report a case where a patient presented at 8 weeks of gestational age with ruptured cornual ectopic pregnancy and hemoperitoneum. Emergency Laparotomy was done and cornual rupture was sutured successfully. Close monitoring of pregnancies in these patients is important to prevent a deleterious delay in treatment of a cornual pregnancy